CLASSROOM VARIABLES AND STUDENT-ATTITUDE TOWARDS SCIENCE: learning by experience - Kumar, David D. (SCHOOL SCIENCE, 2013)
A review of empirical studies reveals a positive relationship between several science classroom variables and student-attitude towards science. The classroom variables include exemplar science curricula, laboratory- centred instruction, laboratory resources and classroom environment. However, there is no conclusive research evidence to establish a relationship between these classroom variables and studentattitude due to discrepancies in the attitude testing instruments utilised.